Dubbing practices in Europe: localisation beats globalisation - Chaume, Frederic (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Whereas new technologies seem to favour globalisation in many areas of translation, dubbing shows a reluctance to embrace this trend of globalisation. Translation memories are now used to make translation easier and faster all over the world. In the area of audiovisual translation, new subtitling software has been developed, which is now widely used among both practitioners and companies. Also in subtitling, most microtextual practices (line segmentation, subtitle segmentation, typographical usages, synthesis of information, etc.) are followed by the majority of professionals. But dubbing seems to refuse to bend to homogenisation. Perhaps due to notions of nationalism and singularity attached to this concept, dubbing still shows different macro- and microtextual practices in the European countries in which it is the most popular type of audiovisual translation.This paper examines four different dubbing practices at a microtextual level -those carried out in Germany, Italy, Spain and France. Before considering new failed attempts to globalise this practice, and also some major advances brought by new technologies, the paper focuses on the differences in layout, take segmentation and dialogue writing in these four countries. These differences show that dubbing practices are still very conservative, and resistant to change and homogenisation.